(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The purpose of this paper is to explore how elements from environment is used as logos by different famous brands. A logo is a graphic mark, emblem, sign, symbol, motif or stylized name used to identify a company, organization, product or brand. It helps the producer to communicate their unique identity and capture consumer’s attention. Almost every brand has a history and some interesting concepts for designing a logo after they came up with the amazing and convincing logo. This research paper has helped to find how brands relate their logo with the elements of environment some examples are – Apple, Dabur, Unilever, Frooti, Wipro etc. Not only Indians foreign countries are also using elements from environment as their logos eg – apple, adidas etc. An attractive logo can easily grab viewer’s attention and communicate a company’s core values in an interesting way. Environment related business use different types of elements from environment some of these are trees, flowers, fruits, vegetables mountains etc. By using these elements from environment it gives company a nature friendly brand identity. Also the use of green colour in a logo symbolizes that the company is an environmentally friendly company. Every element in a logo has to be perfect in order to convey the right message to the viewers. For instances Dabur has replaced its age old brand identity of banyan tree with a new, younger, colourful and vibrant tree. The tree trunk is in the form of three people with their arms raised conveying the happiness in achievement. The broad trunk represents stability and its multiple branches represent growth. The logo of the Indian Air Force has a Himalayan Eagle, within a round placed directly below the State Emblem of India. The Himalayan Eagle symbolizes victory, longevity, speed, pride, royalty. It also symbolizes the fighting qualities of the Indian Air Force.